The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2217/imt.15.30
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunoglobulin (KIOVIG ® /GAMMAGARD LIQUID ® ) for Immunodeficiency and Autoimmune Diseases: An Observational Cohort Study

Abstract: In this observational study, the efficacy and safety of IVIG 10% in routine clinical practice was similar to that previously reported in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…Nausea and dizziness were also reported. Such events, together with other minor hypersensitivity reactions involving symptoms such as fevers and chills, are consistent with previously reported studies of octagam® 10% [8], and other ready-to-use liquid preparations of IVIG 10% [9][10][11] and IVIG 5% [12][13][14] in patients with ITP. As was observed with the patients with ITP treated with octagam® 10% in our subgroup analysis, ADRs associated with IVIG are generally transient and of mild-tomoderate severity [8][9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nausea and dizziness were also reported. Such events, together with other minor hypersensitivity reactions involving symptoms such as fevers and chills, are consistent with previously reported studies of octagam® 10% [8], and other ready-to-use liquid preparations of IVIG 10% [9][10][11] and IVIG 5% [12][13][14] in patients with ITP. As was observed with the patients with ITP treated with octagam® 10% in our subgroup analysis, ADRs associated with IVIG are generally transient and of mild-tomoderate severity [8][9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 91%
“…The guideline-recommended dose of IVIG for ITP is a total cumulative dose of 2 g/kg body weight divided over either 2 days (1 g/kg/day) [15]. The frequency of ADRs in this study also compared favourably to the results of a previously reported PASS study investigating the safety of another ready-to-use IVIG 10% liquid preparation in the treatment of ITP, where the incidence of ADRs was 46% [9]. The incidence of ADRs in the current and previous PASS studies was well within the upper range of ADR rates reported for IVIG preparations [15].…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, in a 2-year prospective, observational study in 117 patients with PID, with a total of 1,765 infusions (Octagam ® (Octapharma, Langenfeld, Germany), Tegeline ® (LFB-Biomedicaments, Les Ulis, France), Immunoglobulin ® (GCC, Suwon-City, Korea), Flebogama ® (Grifols, S.A., Barcelona, Spain), Vigam ® (Bio Products Laboratory Limited (BPL), Hertfordshire, UK), Kiovig ® (Baxter AG, Vienna, Austria), immediate infusion-related adverse reactions occurred in 38 of 1,765 infusions (2.15%), most commonly chills, fever, headache, nausea, malaise, and myalgia [17]. A recent observational study in 88 subjects with immunodeficiency or acute autoimmune diseases receiving IVIG 10% (Kiovig ® ) reported 67 ADRs in 27 subjects (30.6%), which were mild to moderate in intensity and mostly transient; the most frequent ADRs reported in this study were headache, pyrexia, vomiting, and chills [18]. In a multicenter, prospective, non-interventional study in 1,313 patients who were given a total of 21,995 Intratect ® (Biotest AG, Dreieich, Germany) infusions, there were 225 events attributed to Intratect ® , resulting in an ADR rate of 1.0% per infusion [19].…”
Section: Discussionmentioning
confidence: 76%
“…; Blazek et al. ]) do not assess their results according to patient's age. Clinical study population analyses reported in the literature have shown that children and elderly may be more susceptible to AEs of treatments in general (Woods et al.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is important to consider that all children were included in the 10% product group, of which 46.2% experienced treatmentrelated AEs compared with 15.8% of adults in the same 10% group. Regrettably, when it came to the interpretation of the impact of age on infusion-related AEs in the 10% treatment group, it was difficult since the published studies reporting safety of 10% IVIG products in adults and children (whether in PID/SID [Church et al 2006;Gelfand and Hanna 2006;Stein et al 2009;Sleasman et al 2010;Wasserman et al 2012;Blazek et al 2015;Krivan et al 2015] or in autoimmune disease [Robak et al 2009;Blazek et al 2015]) do not assess their results according to patient's age. Clinical study population analyses reported in the literature have shown that children and elderly may be more susceptible to AEs of treatments in general (Woods et al 2005;Priyadharsini et al 2011;Alomar 2014).…”
Section: Discussionmentioning
confidence: 99%